1995
DOI: 10.3109/00365599509180550
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Arm Arterio-Venous Fistula—an Alternative for Vascular Access in Haemodialysis

Abstract: Forty-eight consecutive arteriovenous fistulae of the upper arm constructed in 44 patients between 1983 and 1987 were reviewed. The median observation time was 8.5 months (range 1 day-65 months). The overall patency rate for fistulae used for haemodialysis (early failures excluded) was 50% after one year and 38% after two years. However, only six (18.7%) of the used fistulae stopped because of thrombosis. The total number of thromboses was nine (19.6%). The main cause of discontinuance of fistulae was a high n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this type of anastomoses, the rates of remaining patent of anastomoses created in the proximity of the upper extremities are found to be higher than those made in the distal upper extremities. In anastomoses made at the distal upper extremities, (Brescia-Cimino; snuff-box) patency rates in the first 6 postoperative months are reported as 66% and 70%, respectively [7,12,14,15]. In our study the patency rate at the end of the first 6 months was 89%.…”
Section: Discussionmentioning
confidence: 44%
“…In this type of anastomoses, the rates of remaining patent of anastomoses created in the proximity of the upper extremities are found to be higher than those made in the distal upper extremities. In anastomoses made at the distal upper extremities, (Brescia-Cimino; snuff-box) patency rates in the first 6 postoperative months are reported as 66% and 70%, respectively [7,12,14,15]. In our study the patency rate at the end of the first 6 months was 89%.…”
Section: Discussionmentioning
confidence: 44%
“…Higly occlusion rates of AVF were reported in ESRD patients in the literature [16,17]. Gade et al have reported that the overall patency rate for AVF used for haemodialysis was 50% after one year and 38% after two years in their study after arterio-venous fistula prosedure [16].…”
mentioning
confidence: 85%
“…Gade et al have reported that the overall patency rate for AVF used for haemodialysis was 50% after one year and 38% after two years in their study after arterio-venous fistula prosedure [16]. They have suggested that the upper arm arteriovenous fistula can serve as a second choice, when a radio-cephalic fistula fails.…”
mentioning
confidence: 99%
“…If a wrist fistula is not possible, options at the elbow (brachiocephalic, transposed brachiobasilic, autogenous vein transfers) can be pursued [3][4][5]. When the elbow or antecubital veins cannot be used to create an AVF, the end of the cephalic vein can be mobilized and tunneled for an anastomosis with the proximal, aboveelbow brachial artery.…”
Section: Choice Of Access Type: Why Avf?mentioning
confidence: 99%